2019
DOI: 10.1108/jmp-06-2018-0270
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the decline of tipping norms in the gig economy

Abstract: Purpose Advances in information technology have enabled new ways of organizing work and led to a proliferation of what is known as the “gig economy.” While much attention has been paid to how these new organizational designs have upended traditional employee–employer relationships, there has been little consideration of how these changes have impacted the social norms and expectations that govern the relationship between workers and consumers. The purpose of this paper is to consider the social norm of tipping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…found that gig workers tend to receive smaller tips than do standard employees. Furthermore, tips have less effect on gig service quality than they do when the service is provided by standard employees (Duhaime & Woessner, 2019). If tipping declines, of course, this could signal a significant loss in take-home pay.…”
Section: Psychology Of Gig Workmentioning
confidence: 99%
See 2 more Smart Citations
“…found that gig workers tend to receive smaller tips than do standard employees. Furthermore, tips have less effect on gig service quality than they do when the service is provided by standard employees (Duhaime & Woessner, 2019). If tipping declines, of course, this could signal a significant loss in take-home pay.…”
Section: Psychology Of Gig Workmentioning
confidence: 99%
“…In an interesting series of four studies, Duhaime and Woessner (2019) found that gig workers tend to receive smaller tips than do standard employees. Furthermore, tips have less effect on gig service quality than they do when the service is provided by standard employees (Duhaime & Woessner, 2019). If tipping declines, of course, this could signal a significant loss in take-home pay.…”
Section: Adapting To Gig Work: Implications For Organizations and For...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, despite the lack of experience in performing new job, the motivation and determination of the gig workers also become the additional issue that could be disputed. As the job features, the company in gig economy has low control towards the quality of services performs by the gig workers (Duhaime et al, 2019). Both sides of the gig workers and company has different expectation especially in the service-based company with temporary connection based on the availability of the job.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, tipping has been shown to increase demand by raising perceptions of superior service quality and reducing perceived expensiveness of the service (Lynn, 2019; Lynn et al, 1993; Lynn & Wang, 2013). Hence, tipping features enable technology platforms to address driver remuneration and customer perceptions (Duhaime & Woessner, 2019), which both have performance‐enhancing properties.…”
Section: Literature Reviewmentioning
confidence: 99%